Using patients’ experiences of adverse events to improve health service delivery and practice: protocol of a data linkage study of Australian adults age 45 and above - Walton, Merrilyn (BMJ Publishing Group, 2014)
INTRODUCTION: Evidence of patients’ experiences is fundamental to creating effective health policy and service responses, yet is missing from our knowledge of adverse events. This protocol describes explorative research redressing this significant deficit; investigating the experiences of a large cohort of recently hospitalised patients aged 45 years and above in hospitals in New South Wales (NSW), Australia. METHODS AND ANALYSIS: The 45 and Up Study is a cohort of 265 000 adults aged 45 years and above in NSW. Patients who were hospitalised between 1 January and 30 June 2014 will be identified from this cohort using data linkage and a random sample of 20 000 invited to participate. A cross-sectional survey (including qualitative and quantitative components) will capture patients’ experiences in hospital and specifically of adverse events. Approximately 25% of respondents are likely to report experiencing an adverse event. Quantitative components will capture the nature and type of events as well as common features of patients’ experiences. Qualitative data provide contextual knowledge of their condition and care and the impact of the event on individuals. Respondents who do not report an adverse event will report their experience in hospital and be the control group. Statistical and thematic analysis will be used to present a patient perspective of their experiences in hospital; the characteristics of patients experiencing an adverse event; experiences of information sharing after an event (open disclosure) and the other avenues of redress pursued. Interviews with key policymakers and a document analysis will be used to create a map of the current practice. ETHICS AND DISSEMINATION: Dissemination via a one-day workshop, peer-reviewed publications and conference presentations will enable effective clinical responses and service provision and policy responses to adverse events to be developed.